Syriac and Garshuni Graffiti at the Monastery of St. Macarius (Wādī al-Naṭrūn, Egypt) - Butts, Aaron Michael (The journal of Eastern Christian studies, 2025)
This article presents three Syriac-script graffiti - two in the Syriac language and one in Arabic - found at the Monastery of St. Macarius in the Wādī al-Naṭrūn (Egypt). These graffiti attest to periodic visits of Syriac Christians to this Coptic monastery at various times in the sixteenth century - when the graffiti were written - as well as probably in the fifteenth - with the report of a (future) Syriac patriarch’s visit at that time. It is proposed that this patriarch is likely to have been Yuḥanon bar Shayullah, who was elected in 1484 and who is reported in other sources to have visited the Wādī al-Naṭrūn, including specifically the Monastery of St. Macarius, before he became patriarch.